Imperatorin and β-sitosterol have synergistic activities in alleviating collagen-induced arthritis. Issue 2 (11th May 2020) - Guo, Qingqing; Li, Li; Zheng, Kang; Zheng, Guang; Shu, Haiyang; Shi, Yingjie; Lu, Cheng; Shu, Jun; Guan, Daogang; Lu, Aiping; He, Xiaojuan
Abstract: Rheumatoid arthritis (RA) is a chronic disease with complex molecular network of pathophysiology, single drug is usually not full satisfactory because it is almost impossible to target the whole molecular network of the disease. Drug combinations that act synergistically with each another is an effective strategy in RA therapy. In this study, we aimed to establish a new strategy to search effective synergized compounds from Chinese herbal medicine (CHM) used in RA. Based on multi‐information integrative approaches, imperatorin (IMP) and β‐sitosterol (STO) were predicted as the most effective pair for RA therapy. Further animal experiments demonstrated that IMP+STO treatment ameliorated arthritis severity of collagen‐induced arthritis (CIA) rats in a synergistic manner, whereas IMP or STO administration separately had no such effect. RNA sequencing and IPA analysis revealed that the synergistic mechanism of IMP+STO treatment was related to its regulatory effect on 5 canonical signaling pathways, which were not found when IMP or STO used alone. Moreover, LTA, CD83, and SREBF1 were 3 important targets for synergistic mechanism of IMP+STO treatment. The levels of these 3 genes were significantly up‐regulated in IMP+STO group compared to model group, whereas IMP or STO administration separately had no effect on them. In conclusion, this study found that IMP and STO were 2 synergistic compounds from the CHM in RA therapy, whose synergistic mechanism was closely related to regulate the levels of LTA, CD83, and SREBF1. Graphical Abstract: Imperatorin and beta‐sitosterol, two synergistic compounds from Chinese herbal medicine, were an effective pair in rheumatoid arthritis therapy.